Zwei zusätzliche Bemerkungen zu pBerlin 15765a - Bojowald, Stefan.
In this contribution, some new thoughts concerning pBerlin 15765a are offered. In the first case, more parallels for the writing km3 for km are presented. In the second case, the defective writing tr for twr is treated adequately. A basis for a reasoned discussion of the loss of w is provided. The phrase cf n twr “knife of reed” is compared to sfd g3s “knife of rush” in the Late Egyptian “Tale of the Two Brothers.”   doi: http://dx.doi.org/10.5913/jarce.53.2017.a014